Artificial insemination with frozen‐thawed boar sperm. Issue 9 (19th June 2017) - Yeste, Marc; Rodríguez‐Gil, Joan E.; Bonet, Sergi
Abstract : Artificial insemination with frozen‐thawed semen in pigs is not a routine technique; its use is restricted to specific cases, such as preservation of valuable genetic material (germplasm banks), safety strategies in case of natural disasters, long‐distance transport of sperm, and in combination with sex‐sorting. Cryoinjuries resulting from freeze‐thawing protocols are a major concern with regard to the fertilization capacity of the treated sperm, which is lower than that of liquid‐stored semen. Here, we provide an overview of artificial insemination using cryopreserved sperm, and summarize the factors that influence cryopreservation success before, during, and after freeze‐thaw (i.e., sperm selection before starting the cryopreservation process, holding time, use of cryoprotectants, and rates of freezing and thawing) and that are driving the identification of biomarkers to predict sensitivity to cryodamage. Three different artificial insemination techniques (conventional or intracervical; intrauterine; and deep intrauterine) are also discussed with regards to their relevance when using frozen‐thawed semen. Finally, we review the use of additives to freezing and thawing media, given reports that they may maintain and improve the quality and fertilizing capacity of frozen‐thawed sperm. In sum, artificial insemination with frozen‐thawed boar sperm can provide reasonable fertility outcomes, if freezable ejaculates, specific additives, and appropriate insemination techniques are used.